"Abject dictatorship of the flesh" : corporeality in the fiction of Patrick White - Grogan, Bridget Meredith (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2013)
Thesis embargoed for an indefinite period - full text not available
Keywords: White, Patrick, 1912-1990 -- Criticism and interpretation; Human body in literature; Dualism in literature; Human body -- Social aspects; Body image -- Social aspects; Australian fiction -- 20th century -- History and criticism